The Deradicalization Paradox: When Former Terrorists Become Perpetrators of Economic Crimes - Sofyan, Muhammad; Priyanto, Sapto (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This study investigates the paradoxical emergence of